ANALISIS KELAIKAN FUNGSI JALAN NASIONAL SECARA TEKNIS DI PROVINSI DAERAH ISTIMEWA YOGYAKARTA (Studi Kasus: Beberapa Ruas Jalan Nasional di Provinsi Daerah Istimewa Yogyakarta) - Haris Firdaus; Latief Budi Suparma; M. Fauzie Siswanto (Universitas Quality, 2022)
A roadway is an infrastructure land required to have a Certificate of Worthiness as a requirement for the roadway to operate in the public interest and a guarantee that the roadway could provide safety, security, and legal certainty for the user and road organizer. The purpose of this study is to analyze the roadworthiness of several National Roads in the Special Region of Yogyakarta, i.e., 006 Kulon Progo City Boundary Section - Yogyakarta (11.21), 008 Yogyakarta - Piyungan Section (8,760), 016 Section City Boundary Sleman - Yogyakarta (5,644), with a total length of 25.614 km. Further analysis was conducted to find out the recommendations for repairs, additions, and maintenance on sections of roads that are not in accordance with the technical standards. The research was conducted by observing existing field conditions based on The Road Function Feasibility Implementation Instructions No. 09/P/BM/2014 Directorate General of Highways Ministry of Public Works. The results of the research on 3 (three) national roads conclude that: (006) Kulon Progo – Yogyakarta City Boundary, (008) Yogyakarta – Piyungan, (016) Sleman – Yogyakarta City Boundary everything has conditional function-worthy categories with recommendations (LS). The eligibility category further action for each road section is to provide recommendations for repair, addition, and maintenance in every technical test that does not fulfill the technical testing standard